1993
DOI: 10.2105/ajph.83.9.1311
|View full text |Cite
|
Sign up to set email alerts
|

Occupation as a risk identifier for breast cancer.

Abstract: OBJECTIVES. Breast cancer mortality may be reduced if the disease is detected early through targeted screening programs. Current screening guidelines are based solely on a woman's age. Because working populations are accessible for intervention, occupational identification may be a way of helping to define and locate risk groups and target prevention. METHODS. We used a database consisting of 2.9 million occupationally coded death certificates collected from 23 states between 1979 and 1987 to calculate age-adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 35 publications
6
51
0
Order By: Relevance
“…For example, Ambrosone et al (14) have reported greatly elevated risk among women who were slow acetylators (deficient in NA T2) who also had a long history of heavy cigarette smoking. This is consistent with observations that persons who lack the capacity to acetylate aromatic amines are at greater risk for bladder cancer following exposure to aniline dyes (15 (17)(18)(19) and correlations with occupational exposures (20)(21)(22) …”
Section: Mechanistic Considerationssupporting
confidence: 91%
“…For example, Ambrosone et al (14) have reported greatly elevated risk among women who were slow acetylators (deficient in NA T2) who also had a long history of heavy cigarette smoking. This is consistent with observations that persons who lack the capacity to acetylate aromatic amines are at greater risk for bladder cancer following exposure to aniline dyes (15 (17)(18)(19) and correlations with occupational exposures (20)(21)(22) …”
Section: Mechanistic Considerationssupporting
confidence: 91%
“…occupational status, was related to high risks of breast cancer [17][18][19][20][21] . One of the most consistent results of previous studies was that increased risk of breast cancer was found among women with professional and managerial occupations [21][22][23][24][25][26][27][28] . Increased risk of breast cancer has also been found for specific job titles in this category, particularly nurses and teachers [21][22][23][24][25][26][27] .…”
Section: Discussionsupporting
confidence: 61%
“…[4][5][6][7][8][9][10][11][12][13][14] The positions most frequently reported are teachers 6,7,9,12,13 administrative workers,4'6"12 religious workers,4'6'9 and health care workerS.67 '9"10"4 Record linkage between the Swedish cancer registry and a population registry comprising all individuals included in the 1970 census (with information on occupation and residence in 1970, occupation in 1960, and date ofdeath) rendered it possible to construct a retrospective cohort that was followed up over a 19-year period. The goal of the present study was to estimate the occupation-specific risk of breast cancer among the female members of this cohort.…”
mentioning
confidence: 99%